Zoonimia y vernácula en Yucuna - Defler Thomas R.; Yucuna Celestino; Bennett Sara (Caldasia)
A glossary of animal names in the Yucuna language from the region of the lower Caquetá river, Mirití-Paraná and the lower Apaporis river (Amazonas and Vaupés departments, Colombia) is presented along with their scientifie binomials. The list includes 274 names and variations for 218 animals of the region. Se presenta una lista de nombres vernáculos de animales en lengua Yucuna de la región del bajo río Caquetá, Mirití-Paraná, bajo río Apaporis (Departamentos de Amazonas y Vaupés, Colombia), con sus correspondientes binomios científicos. Se incluyen 274 nombres para 218 animales de la región.